Concurrence of CareStart™ Malaria HRP2 RDT with microscopy in population screening for Plasmodium falciparum infection in the Mount Cameroon area: predictors for RDT positivity - Teh, Rene Ning (Trop Med Health, 2019)
BACKGROUND: Malaria remains a diagnostic challenge in many endemic communities. Although rapid diagnostic tests (RDTs) are presently widely used for malaria diagnosis, there is a dearth of information on post-marketing surveillance on its efficacy in Cameroon. The present study evaluated the performance characteristics of CareStart™ Malaria HRP2 (histidine-rich protein 2) antigen (Ag) RDT in diagnosing Plasmodium falciparum infection in the Mount Cameroon area and predictors associated with RDT positivity. METHODS: The CareStart™ Malaria HRP2 Plasmodium falciparum (G0141) Ag RDT was evaluated in a cross-sectional community-based survey involving 491 children of both sexes aged 6 months to 14 years between April and May 2018. Malaria parasitaemia was confirmed by light microscopy. Sensitivity (Se), specificity (Sp), positive (PPV) and negative (NPV) predictive values of the RDT, and the corresponding accuracy and Kappa value (κ) were determined using microscopy as the gold standard. Haemoglobin (Hb) concentration was obtained using an auto-haematology analyser. Results were compared using the chi-square test and associations between predictor variables, and RDT results were assessed using logistic regression analysis. RESULTS: Microscopically confirmed malaria parasite prevalence was 27.7%, and geometric mean density was 187 parasites/μL of blood (range 70–1162). Se, Sp, PPV, NPV and accuracy were 82.4, 76.6, 57.4, 91.9 and 78.2%, respectively. Sensitivity depended on parasitaemia and reached 96.1% at densities ≥ 200 parasites/μL of blood. The accuracy of malaria parasitaemia (as assessed by the area under the receiver operating characteristic curve) to predict malaria by RDT was 75.4% (95% CI 70.6–80.1). The agreement between microscopy and RDT was moderate (κ = 0.52). RDT positivity was significantly associated with fever (P < 0.001), children less than 5 years (P = 0.02), history of fever within a month (P < 0.001) and anaemia (P = 0.002). CONCLUSION: The overall concurrence of CareStart™ Malaria HRP2 pf Ag RDT with microscopy in the detection of P. falciparum infection is moderate and is most useful at parasitaemia ≥ 200 parasites/μL of blood and presentation with fever. While RDT is effective as a diagnostic test for confirmation of clinical cases of malaria, its applications in population screening with a higher proportion of asymptomatic cases are limited.